A cross-sectional study of the prevalence of intensity of infection with Schistosoma japonicum in 50 irrigated and rain-fed villages in Samar Province, the Philippines - Gonzales Ryan O'Neil; Alday Portia; Joseph Lawrence; Tallo Veronica; Bélisle Patrick; Carabin Hélène; Balolong Ernesto; Tarafder Mushfiqur R; Riley Steven; Olveda Remigio; McGarvey Stephen T (BMC, 2006)
Abstract Background Few studies have described heterogeneity in Schistosoma japonicum infection intensity, and none were done in Philippines. The purpose of this report is to describe the village-to-village variation in the prevalence of two levels of infection intensity across 50 villages of Samar Province, the Philippines. Methods This cross-sectional study was conducted in 25 rain-fed and 25 irrigated villages endemic for S. japonicum between August 2003 and November 2004. Villages were selected based on irrigation and farming criteria. A maximum of 35 eligible households were selected per village. Each participant was asked to provide stool samples on three consecutive days. All those who provided at least one stool sample were included in the analysis. A Bayesian three category outcome hierarchical cumulative logit regression model with adjustment for age, sex, occupation and measurement error of the Kato-Katz technique was used for analysis. Results A total of 1427 households and 6917 individuals agreed to participate in the study. A total of 5624 (81.3%) participants provided at least one stool sample. The prevalences of those lightly and at least moderately infected varied from 0% (95% Bayesian credible interval (BCI): 0%-3.1%) to 45.2% (95% BCI: 36.5%-53.9%) and 0% to 23.0% (95% BCI: 16.4%-31.2%) from village-to-village, respectively. Using the 0-7 year old group as a reference category, the highest odds ratio (OR) among males and females were that of being aged 17-40-year old (OR = 8.76; 95% BCI: 6.03-12.47) and 11-16-year old (OR = 8.59; 95% BCI: 4.74-14.28), respectively. People who did not work on a rice farm had a lower prevalence of infection than those working full time on a rice farm. The OR for irrigated villages compared to rain-fed villages was 1.41 (95% BCI: 0.50-3.21). Discussion We found very important village-to-village variation in prevalence of infection intensity. This variation is probably due to village-level variables other than that explained by a crude classification of villages into the irrigated and non-irrigated categories. We are planning to capture this spatial heterogeneity by updating our initial transmission dynamics model with the data reported here combined with 1-year post-treatment follow-up of study participants.